Isolated Fallopian Tube Torsion With Fimbrial Cyst In A 10 Year-old Girl Diagnosed By Ultrasound: A Case Report - Ormasa, Maria Constancia Olveda (J Radiol Case Rep, 2015)
Torsion of the fallopian tube without the involvement of the ipsilateral ovary is a rare but important cause of acute abdominal pain in women as it is a surgical emergency. Although uncommon, it should be considered as one of the differential diagnosis in female children presenting with acute lower abdominal or pelvic pain. The diagnosis of isolated fallopian tube torsion is difficult pre-operatively and is often made during laparoscopic or surgical exploration because diagnostic features are usually non-specific. In this report, we present a case of isolated fallopian tube torsion with fimbrial cyst in a young female patient diagnosed pre-operatively by ultrasound.